Correlation of Effects of Erythromycin Analogues on Intact Bacteria and on [(14)C]Erythromycin Binding to Escherichia coli Ribosomes - Pestka, Sidney (Antimicrob Agents Chemother, 1974)
The dissociation constants for binding to ribosomes from Escherichia coli and concentrations at which 50% inhibition of [(14)C]erythromycin binding to ribosomes occurred were determined for 45 erythromycin analogues. These values were correlated with their antibacterial activities against Bacillus subtilis. Compounds which bound to ribosomes best showed the greatest activities; those which were poorly bound to ribosomes showed little or no antibacterial activity. The ribosomal binding assays therefore reflected the general antibacterial potential of the erythromycin analogues.